Nonlinear Frequency Scaling Algorithm for High Squint Spotlight SAR Data Processing. (3rd April 2008) - Jin Jin, Lihua Lihua; Liu Liu, Xingzhao Xingzhao
Abstract : This paper presents a new approach for the squint-mode spotlight SAR imaging. Like the frequency scaling algorithm, this method starts with the received signal dechirped in range. According to the geometry for the squint mode, the reference range of the dechirping function is defined as the range between the scene center and the synthetic aperture center. In our work, the residual video phase is compensated firstly to facilitate the following processing. Then the range-cell migration with a high-order range-azimuth coupling form is processed by a nonlinear frequency scaling operation, which is different from the original frequency scaling one. Due to these improvements, the algorithm can be used to process high squint SAR data with a wide swath and a high resolution. In addition, some simulation results are given at the end of this paper to demonstrate the validity of the proposed method.